To the knowledge of the aphidiine wasps (Hymenoptera: Braconidae: Aphidiinae) from China - Davidian, Elena M.; Belokobylskij, Sergey A. (Zootaxa, 2024)
A new species of the aphidiine parasitoid Binodoxys yunnanicus Davidian, sp. nov. is described and illustrated from Yunnan Province, China. This species is characterised by long filiform antenna, large wings, narrow petiole of metasoma, long ovipositor sheaths, and almost straight prongs with four long setae on their dorsal margin and one long apical bristle. Praon longistigmus Davidian, 2020, described from Sichuan Province of China, is synonymised with Astigmapraon hei Tian et Chen, 2017 (syn. nov.).